1990
DOI: 10.1111/j.1476-5381.1990.tb15797.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bronchodilator properties of Ro 31–6930, a novel potassium channel opener, in the guinea‐pig

Abstract: 1Ro 31-6930 (0.001-0.3 MM), cromakalim (0.03-3.0OUM), salbutamol (0.001-0.3 pM) and theophylline (0.3-100pM) evoked dose-related reductions in guinea-pig spontaneous tracheal tone with IC,0 values of 0.044, 0.20, 0.021 and 21.OpM respectively. All four agents also relaxed tone supported by betahistine, carbachol, 5-hydroxytryptamine (5-HT), leukotriene D4 (LTD4), U46619 and prostaglandin D2 (PGD2). The order of potency of tracheal relaxants was always salbutamol > Ro 31-6930 > cromakalim > theophylline. 2 All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In the present study, the IC50 of levcromakalim was in agreement with other reports using vascular and airway smooth muscle [9,[26][27][28][29]; it was more potent than THEO. However, levcromakalim cannot be a first-line regimen for bronchodilatation, since the β-adrenergic agonist, ISO, was much more potent than levcromakalim in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, the IC50 of levcromakalim was in agreement with other reports using vascular and airway smooth muscle [9,[26][27][28][29]; it was more potent than THEO. However, levcromakalim cannot be a first-line regimen for bronchodilatation, since the β-adrenergic agonist, ISO, was much more potent than levcromakalim in this study.…”
Section: Discussionsupporting
confidence: 82%
“…However, levcromakalim cannot be a first-line regimen for bronchodilatation, since the β-adrenergic agonist, ISO, was much more potent than levcromakalim in this study. The relationship between the three bronchodilators, β-adrenergic agonist, KATP openers and THEO supports the results reported by PACIOREK et al [27], where the order of guinea-pig tracheal relaxants was always salbutamol > Ro 31-6930 (a potassium channel opener) > cromakalim > THEO.…”
Section: Discussionsupporting
confidence: 79%
“…Distribution of KC 128-sensitive K+ channel in various airway tissues Generally, ATP-sensitive K+ channel openers, including levcromakalim, have been reported to be not very effective on cholinoceptor agonist-induced contraction in the guinea-pig tracheal smooth muscle (Allen et al, 1986;Nielsen-Kudsk et al, 1988;Paciorek et al, 1990;Taylor et al, 1992;Imagawa et al, 1993). It has also been reported that the relaxant effects of K+ channel openers in airway tissues were largely dependent on the concentration of agonist used (Raeburn & Brown, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of potassium channel openers in suppressing the tone of airway smooth muscle in vitro are well established (Allen et al, 1986;Bray et al, 1987;Arch et al, 1988;NielsenKudsk et al, 1988;Paciorek et al, 1990;Berry et al, 1991;Raeburn & Brown, 1991). The effects of potassium channel openers on neurally-mediated responses in the airways have also attracted interest.…”
Section: Introductionmentioning
confidence: 99%